Analisis Perbandingan Algoritma Pada Tiktok dan Instagram Sebagai Content Media Dalam Pemasaran - A.Irma Putri Meilina Manullang; Yahfizham Yahfizham (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Technological advances have made social media a marketing platform that many people are interested in. Various applications already have marketing features such as the TikTok and Instagram applications. By utilizing content as a marketing medium for a brand or product owned on the TikTok and Instagram applications. This research was carried out using a literature study method through previous journals related to the problem. The aim of this research is to find similarities and differences between the TikTok and Instagram application algorithms as marketing media. The results of this research are that the TikTok and Instagram applications have the same advantages in marketing an item or product, namely making the content as interesting as possible to attract the enthusiasm of the general public online.